PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP MOTIVASI BELAJAR SISWA SD KELAS III PEMBELAJARAN BAHASA INDONESIA - Feby Kharisna; Nur Azmi Alwi; Andika Surya Perdana; Nadiah Sya’idah (Cerdas Proklamator, 2021)
This research aims to determine the effect of students' learning motivation through the application of the scramble learning model. This research is a research design with non-equivalent control group design, and quantitative research in the form of quasi-experimental research. This research was conducted at SDN 18 Lembah Melintang, Pasaman Barat. The population of this research is the third grade students of SDN 18 Lembah Melintang in the academic year 2021/2022. The samples of this study were 28 students in class IIIA and 26 students in class IIIB. The sampling technique used is "saturated sampling". Data analysis technology uses quantitative descriptive statistics to compare the average score of the final questionnaire on the Learning Motivation Scale with the help of Microsoft Excel. The results showed that the average final questionnaire for the control class was 97, while the average for the experimental class was 99. The results of the independent t-test analysis above can be seen the value of Sig. (2-tailed) of 0.000<0.05, it can be concluded that there is a significant difference in students' learning motivation in the control class and the experimental class. Therefore, it can be concluded that the Scramble learning mode will affect the learning motivation of third grade students at SDN 18 Lembah Melintang, so teachers must be able to use scramble learning mode to convey learning, because this learning mode has been proven to improve students' learning abilities and motivation.